IMPROVING ACCESS AND QUALITY OF EDUCATION IN ISOLATED AREAS: A LITERATURE REVIEW - Loso Judijanto; Ismaul Fitroh; Ansori Ansori (JOURNAL OF COMMUNITY DEDICATION, 2023)
Improving access to and quality of education in isolated areas has become an important focus in the global education discourse. The purpose of this literature review is to analyze the various strategies that have been implemented and find out their effectiveness in overcoming education problems in remote areas. The method used in this study is the literature research method. The results show that technology integration such as the use of e-learning and online learning platforms plays a vital role in improving the affordability of education. Meanwhile, active participation of local communities and collaboration between the government, private sector and non-profit organizations are proven to improve the quality and relevance of education provided. Training and professional development strategies for teachers in isolated areas are also key to improving the quality of education provided.